Processing thermoplastic matrix towpregs by pultrusion - Nunes, J. P. (2011)
In this work glass fibre reinforced polypropylene (GF/PP) towpregs, continuously produced at different processing conditions in a dry powder coating equipment, were processed into final composites by using a developed prototype pultrusion equipment. The influence of the fibre pull-speed and furnace temperature used in the dry coating towpregger on the polymer content of final produced towpregs was determined. Optical microscopy and SEM were techniques also used to assess quality of the produced GF/PP towpregs. The GF/PP towpregs were then processed into a composite bar by using a prototype pultrusion machine that will be described and presented in the workshop. Studies were carried out to determine the influence of the pull-speed and temperatures used in the pultrusion heated and cooled dies on the mechanical and other relevant physical properties of final composite profiles. Finally, the final composite profiles processing window and optimisation will be discussed and presented.